MiR-1539 and Its Potential Role as a Novel Biomarker for Colorectal Cancer - Cui, Xueyang; Lv, Zhi; Ding, Hanxi; Xing, Chengzhong; Yuan, Yuan (Frontiers in Oncology, 2021)
Purpose We investigated microRNA (miR) 1539 as a potential biomarker for predicting the risk and pathobiological behavior of colorectal cancer (CRC). Methods Our strategy consisted of analyzing 100 serum samples from 51 CRC patients, 49 healthy controls (HCs), and another 56 CRC tissue and matched normal adjacent to tumor (NAT) samples. The relative expression levels of miR-1539 in exosomes, serum and tissues were detected and compared in the different groups, using reverse transcription-polymerase chain reaction (RT-qPCR). The diagnostic value and potential function of miR-1539 were investigated using clinicopathological data combined with bioinformatics analysis. Results MiR-1539 expression was significantly up-regulated in exosomes (p = 0.003) and cancer tissue (p < 0.001) from CRC patients. MiR-1539 expression levels in serum varied according to different tumor sites (right-sided vs. left-sided, p = 0.047; left-side CRC vs. HCs, p = 0.031). In terms of diagnostic efficacy, miR-1539 expression in exosomes may help distinguish CRC cases from HCs with a sensitivity of 92.2%, and miR-1539 expression in serum may improve the specificity to 96.6% for left-sided CRC diagnosis. When combined with clinicopathological data, serum miR-1539 levels were positively associated with vascular endothelial growth factor (VEGF) expression (p = 0.028), whilst levels in CRC tissue were positively associated with increased Ki-67 levels (p = 0.035). Poorer pathologic differentiation was potentially related to an increased tendency of miR-1539 expression in CRC tissue (p = 0.071). Based on our bioinformatics analysis, miR-1539 may have a significant mechanistic influence on CRC genesis and progression. Conclusions Circulating or tissue based miR-1539 may be used as a novel potential biomarker for CRC screening, and a predictor of poor clinicopathological behavior in tumors.